(untitled) (Comparative & International Education Series, 2021)
Abstract Asian women faculty (AWF)are a growing population while they face various difficulties especially teaching and living in foreign countries. This paper examines the academic and social life experiences of AWF in the United Arab Emirates (UAE), strategies of balancing their work and life in this multicultural and cross-cultural context, as well as their plans and career expectation. The questionnaire and in-depth interviews of 38 AWF members will be conducted. This group represents three non-Islamic Asian countries communities including China, India and the Philippines. The interviews aim to explore their motivations, desires, conflicts, dilemmas and coping strategies during their teaching and living in the UAE. It is expected that this paper will provide a better understanding of AWF teaching and living in the UAE regarding their difficulties and ways to help them. Key word: Asian women faculty transnational context UAE